The influences of hydrology on the radiogenic and stable carbon isotope composition of cave drip water, Grotta di Ernesto (Italy) - Fohlmeister, Jens; Schröder-Ritzrau, Andrea; Spötl, Christoph; Frisia, Silvia; Miorandi, R.; Kromer, Bernd; Mangini, Augusto (Radiocarbon, 2010)
14C and δ13C values of C-containing species in cave drip waters are mainly controlled by the C isotope composition of karst rock and soil air, as well as by soil carbon dynamics, in particular the amount of soil CO2 in the unsaturated soil zone and the process of calcite dissolution. Here, we investigate soil carbon dynamics by analyzing the 14C activity and δ13C values of C dissolved in cave drip water. Monthly over a 2-yr period, we collected drip water from 2 drip sites, one fast and one relatively slow, within the shallow Grotta di Ernesto Cave (NE Italy). The 14C data reveal a pronounced annual cycle. In contrast, the δ13C values do not show an annual pattern and only small interannual variability compared to the δ13C values of soil waters. The annual 14C drip-water cycle is a function of drip-rate variability, soil moisture, and ultimately hydrology.